A REVIEW OF CURRENT IMMUNGDIAGNOSTIC TECHNIQUES IN PROTOZOOLOGY (Journal of Biomedical Investigation, 2010)
Immunodiagnostic techniques are based on the principles of immunochemistry. Current diagnostic methods employed in protozoology include ELISA technique, counter immunoelectrophoretic, immunoblotting technique, immuno-fluorescence Assay methods and complement fixation tests. These methods have been effectively employed in protozoology (exemplified by malaria and Trypanosomiasis). These methods have been found to be effective, sensitive and specific and are useful tools in research and fieldwork especially in manpower-constrained areas of the tropics and sub-tropics
Keywords: Immunodiagnosis; Protozoology; Techniques